Mineral Chemistry of Olivine, Oxy-Spinel, and Clinopyroxene in Lavas and Xenoliths from the Canary, Azores, and Cape Verde Islands (Macaronesia, North Atlantic Ocean): New Data and Comparisons with the Literature - Federica Zaccarini; Giorgio Garuti; Reinhard Moser; Konstantinos Mavrogonatos; Panagiotis Voudouris; Adriano Pimentel; Sabrina Nazzareni (Minerals, 2024)
An electron microprobe study was carried out on olivine, clinopyroxene, and oxy-spinel occurring in basalts and dunite xenoliths from the archipelagos of the Azores, the Canary Islands, and Cape Verde. By comparing our results with previously published data from the volcanic islands of Macaronesia, we confirmed the validity of the compositions of olivine, clinopyroxene, and oxyspinel as geochemical tracers. The origin of olivine, i.e., crystallized in the lithospheric mantle or in volcanic rocks, was successfully discriminated. Olivine from Lanzarote dunite xenoliths, which represent fragments of the mantle transported to the surface by host magmas, exhibited higher Fo% values (Fo91.02 to Fo91.94) and a different distribution of minor elements Ca, Ni, and Mn (CaO up to 0.42 wt%, NiO 0.07–0.41 wt%, MnO 0.06–0.3 wt%) when compared with olivine occurring as phenocrysts in basaltic lavas from the Macaronesian islands. The highly variable forsterite contents (Fo75.1 to Fo94.4) in olivine from gabbro and peridotite xenoliths found across the islands of Macaronesia were attributed to fractional crystallization that started in a deep magma reservoir, suggesting that these xenoliths represent cumulate rocks and not mantle fragments. Alternatively, these xenoliths may have been affected by the interaction with metasomatic fluids. The composition of clinopyroxene phenocrysts was used to decipher formation conditions under extensional tectonics. Their composition suggests that the host lavas have an alkaline to calc-alkaline signature. Furthermore, clinopyroxene euhedral shapes and compositions suggest an origin by fractional crystallization in a closed magmatic system. The composition alone of oxy-spinel from Macaronesian basalts and xenoliths was not sufficient to draw conclusions about the geodynamic environment where they were formed. Nevertheless, the relationship between oxy-spinel and olivine crystallized in equilibrium was successfully used as oxybarometers and geothermometers. The oxy-spinel–olivine pairs show ...